Thermal degradation mechanisms of PEDOT:PSS - Vitoratos, Evangelos G.; Sakkopoulos, Sotirios A.; Dalas, Evangelos; Paliatsas, N.; Karageorgopoulos, Dimitrios; Petraki, Fotini; Kennou, Stella; Choulis, Stelios A. (My University, 2009)
The thermal stability of thin (50 nm) PEDOT:PSS films, was investigated by dc conductivity measurements, X-ray and UV photoelectron spectroscopies as a function of heating temperature and heating time. The mechanism of electrical conductivity as a function of temperature is consistent with a hopping type carrier transport. The electrical conductivity decreased, as a function of time, in agreement with a granular metal type structure, in which aging is due to the shrinking of the PEDOT conductive grains. XPS and UPS spectra indicate that conformational changes of the PEDOT:PSS film are responsible for this behaviour and a model for these modifications is proposed.
Keywords: Conducting polymers; Conductivity degradation mechanisms; Thermal stability; PEDOT/PSS; Organic light emitting diodes; Organic solar cells